Thermophilic bacteria isolated from Mount Merapi, Java, Indonesia as a potential lead bioremediation agent - Anna Rakhmawati; Endang Tri Wahyuni; Triwibowo Yuwono (Society for Indonesian Biodiversity, 2021)
Abstract. Rakhmawati A, Wahyuni ET, Yuwono T. 2021. Thermophilic bacteria isolated from Mount Merapi, Java, Indonesia as a potential lead bioremediation agent. Biodiversitas 22: 3101-3110. Contamination by lead (Pb) has become a serious health and environmental problem, that has to be urgently prevented. Bioremediation is one of the environmentally friendly methods for eliminating Pb from the contaminated environment. This study was aimed to investigate the potency of lead-tolerant thermophilic bacteria isolated from solfatara Mount Merapi, Indonesia. A total of 340 isolates of thermophilic bacteria were screened for lead tolerance at 55 °C. Five bacterial isolates were found to show tolerance to 100 mg/L Pb (II), and then were further evaluated and identified as Aeribacillus pallidus strains MRP112, MRP148, MRP272, MRP278, and MRP280 based on 16S rRNA gene sequences analysis. Among the five isolates, A. pallidus MRP 280 showed highest activity in removing Pb at pH 6, 55°C for 24 h. The analysis of scanning and transmission electron microscopy, biofilm formation, and siderophore production, demonstrated that lead tolerance of A. pallidus MRP 280 strain was also accompanied by morphological changes, bioaccumulation, biosorption, biofilm, and siderophore assembly. In conclusion A. pallidus MRP 280 was demonstrated as one of the most potential bacterial strains, can be recommended as an agent for high-temperature lead bioremediation.